Study on clinical profile and etiology of acute febrile encephalopathy in children aged between 2 months to 14 years attending to a tertiary care hospital, Eluru, Andhra Pradesh, India - Dr. Anusha Deepthi C.H; Dr. Manohar Bekkam (Pediatric Review: International Journal of Pediatric Research, 2018)
Background: Acute febrile encephalopathy (AFE) is a common conditionleading to hospitalization of children in India. CNS infections are commonest cause of non-traumatic coma in children. Although AFE is one of the major causes of hospital admissions of children and adults in India, only a few studies have been done on it so far.So this study was conducted to study the clinical profile and etiology of AFE in children. Methods: This prospective study was carried out on 84 children between 2 months to 14 years, with fever duration of<14 days, GCS ≤12 at the time of admission and altered sensorium in the pediatric intensive care unit over a period of 12 months from August 2017 to August 2018. Clinical profile and etiology were evaluated. Results: Thepresent study, has identified viral encephalitis (38%) and pyogenic meningitis (34.5%) as the major causes of Acute febrile encephalopathy in the study population. Most common symptoms apart from fever and altered sensorium were vomiting (58.3%), convulsions (45.2%), headache (35.7%), jaundice (8.3%), and most common presenting clinical signs apart from fever and GCS< 12 were neck stiffness (52.4%), signs of raised ICT (47.6%), positive Kernig’s sign (39.2%), and motor tone abnormalities (34.5%). Conclusion: In this study, we observed that CNS infections are the most common cause of febrile encephalopathy in children. Early recognition of the clinical signs and immediate and appropriate treatment will combat the problem and improve the survival rate.